2019
DOI: 10.1021/acs.energyfuels.9b00511
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Metallurgical Coke within Minutes through Coal Densification and Microwave Energy

Abstract: This paper shows how feedstock densification gives rise to a step change in the time required to create a metallurgical grade coke using microwave energy. Five densified coking and noncoking coals were heated in a multi-mode microwave 2450 MHz cavity for varying treatment times (2-20 minutes) with a fixed power input (6 kW). Proximate analysis, intrinsic reactivity, coke reactivity, dielectric properties, and petrographic analysis of the coals and microwave produced lump cokes were compared to a commercial lum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…To explore this potential further, washed Valle coal would need to be characterized for its coking potential and tested in pilotscale coking ovens. In addition, novel coking methods, such as microwave technology, 45 have demonstrated that noncoking coals can be coked rapidly, which may facilitate low-grade coking coal to be used in blends to produce high-quality cokes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore this potential further, washed Valle coal would need to be characterized for its coking potential and tested in pilotscale coking ovens. In addition, novel coking methods, such as microwave technology, 45 have demonstrated that noncoking coals can be coked rapidly, which may facilitate low-grade coking coal to be used in blends to produce high-quality cokes.…”
Section: Resultsmentioning
confidence: 99%
“…44 Another consideration is how the coals behave on the stoker furnace bed. Coking coals swell during combustion, 45 while lump thermal coals generally do not. 46 The swelling of lump coal is different from that of small particles of coal.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonaceous materials typically include both graphitizing and nongraphitizing carbons. , Lignite and subbituminous ranks typically belong to nongraphitizing carbon (although thermoplasticity can be induced by microwave heating for some subbituminous samples), and some bituminous and anthracite coals are typically graphitizable to some degree. Anthracite is highly aromatic and can be well-aligned facilitating graphitization .…”
Section: Introductionmentioning
confidence: 99%
“…27) Given the importance of coal briquetting in the ironmaking process, several reports have been published on how the briquetting conditions, such as the compression pressure and the particle diameter affect the strength of the briquette and the coke. [28][29][30][31][32][33] However, those studies were conducted on a trial-and-error basis, while theoretical studies on the briquetting process are few. In recent years, numerical simulation has been used to investigate the behavior of powder materials.…”
Section: Introductionmentioning
confidence: 99%